2020
DOI: 10.1371/journal.pone.0227484
|View full text |Cite
|
Sign up to set email alerts
|

Control of the microsporidian parasite Nosema ceranae in honey bees (Apis mellifera) using nutraceutical and immuno-stimulatory compounds

Abstract: Nosema ceranae is a microsporidian parasite that causes nosemosis in the honey bee (Apis mellifera). As alternatives to the antibiotic fumagillin, ten nutraceuticals (oregano oil, thymol, carvacrol, trans-cinnmaldehyde, tetrahydrocurcumin, sulforaphane, naringenin, embelin, allyl sulfide, hydroxytyrosol) and two immuno-stimulatory compounds (chitosan, poly I:C) were examined for controlling N. ceranae infections. Caged bees were inoculated with N. ceranae spores, and treatments were administered in sugar syrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 64 publications
6
33
0
Order By: Relevance
“…Furthermore, Mayack et al [41] suggested that N. ceranae causes significant regulatory changes in the highly conserved octopamine hormone stress pathway, affecting the bee's life span and possibly their age polyethism. This study showed that both chitosan and peptidoglycan reduced N. ceranae spore counts by more than 60%, which confirms a previous report on chitosan's partial suppression of N. ceranae infections in honey bees [42]. However, although both PAMPs similarly reduced N. ceranae spore counts, chitosan was more effective in increasing survivorship of N. ceranae infected bees.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Mayack et al [41] suggested that N. ceranae causes significant regulatory changes in the highly conserved octopamine hormone stress pathway, affecting the bee's life span and possibly their age polyethism. This study showed that both chitosan and peptidoglycan reduced N. ceranae spore counts by more than 60%, which confirms a previous report on chitosan's partial suppression of N. ceranae infections in honey bees [42]. However, although both PAMPs similarly reduced N. ceranae spore counts, chitosan was more effective in increasing survivorship of N. ceranae infected bees.…”
Section: Discussionsupporting
confidence: 90%
“…0.124 µg of eleutheroside B, 0.055 µg of eleutheroside E and 0.001 µg of naringenin. Nevertheless, the main therapeutic and prophylaxis effect against Nosema infection is probably connected only with eleutherosides as in other studies, naringenin from citrus fruit had a moderate effect on reducing Nosema spore loads and its main advantage was the extension of honeybees’ lifetime [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report of N. ceranae infection in A. mellifera, there has been some controversy about the consequences of such infection. However, in recent years most studies have confirmed that N. ceranae has a pathogenic effect in this host, expressed at least in a shortening of the workers' lifespan in controlled (cage) experiment (e.g., Mayack and Naug, 2009;Alaux et al, 2010;Martín-Hern andez et al, 2011;Dussaubat et al, 2012;Goblirsch et al, 2013;Schwarz and Evans, 2013;Aufauvre et al, 2014;Basualdo et al, 2014;Roberts and Hughes, 2014;2015;Williams et al, 2014;Doublet et al, 2015aHuang et al, 2015; only few papers failing to report this effect (Milbrath et al, 2013;Retschnig et al, 2014;Garrido et al, 2016).…”
Section: Genetic Diversity Of N Ceranaementioning
confidence: 99%
“…Similarly, a mixture of different species belonging to Lactobacillus , Bifidobacteria , Pediococci and Lactococci genera showed no advantageous effect on the infection (Endler, ). Another study including nutraceutical, prebiotic and probiotics showed acacia gum as the most effective prebiotic, although with a high mortality as side effect, and the probiotic Protexin Concentrate© single‐strain (ProtexinC1) as able to reduce the spores, increasing the bee survival (Borges, ).…”
Section: Can N Ceranae Kill a Colony?mentioning
confidence: 99%